Quality of intrapartum and newborn care in public healthcare facilities of Wolkite town, Central Ethiopia: facility-based cross-sectional study - Mulat, Berhanu Semra; Zewdie, Amare; Kasahun, Abebaw Wasie; Gashu, Molla; Nega, Adiam; Melis, Tamirat (Frontiers in Global Women's Health, 2025)
BackgroundQuality of intrapartum and newborn care is increasingly recognized internationally as a critical aspect of the unfinished maternal and newborn health agenda. Although the world has made significant progress in reducing maternal and newborn mortality, there are still far too many preventable and treatable maternal and newborn deaths globally. Poor-quality intrapartum and newborn care along with inadequate access to basic maternal and newborn healthcare services has contributed to high maternal and child mortality in low- and middle-income countries. However, there is not enough evidence describing the status quality of intrapartum and newborn care in Ethiopia, specifically in the study area. Thus, this study aims to assess the quality of intrapartum and newborn care in public health facilities of Wolkite town, Central Ethiopia.MethodsA facility-based cross-sectional study design was conducted from March to April 2023 among five public health facilities, and observation of health service provision was employed among 185 mothers. A consecutive random sampling method was applied. Data were collected through document review, interview, health service provision observation, and health facility audit against the standard checklist. Quality of intrapartum and newborn care was measured using standard intrapartum and newborn care criteria. Thus, good-quality care was considered if the mother and newborn scored 75% or more of the intrapartum criteria during childbirth. Data were entered, coded, and cleaned using EpiData version 4 and exported to SPSS version 25 for analysis. Descriptive summary statistics including proportions, mean, and median were computed to describe study variables. Multivariable logistic regression analysis was performed to identify factors significantly associated with the outcome variable. Finally, adjusted odds ratios with 95% confidence intervals and p-values <0.05 were considered to declare the statistical significance level of a variable.ResultThe study revealed that the level of good quality of intrapartum and newborn care was 35.1% and 69.7%, respectively. Input quality (AOR = 4.52; 95% CI 1.31, 14.98), health workers with 5 or more years of experience (AOR = 7.23; 95% CI 1.49, 35.84), received on job training (AOR = 5.82; 95% CI 1.91, 13.61), and friendly maternal and newborn care (AOR = 6.89; 95% CI 1.34, 35.62) were significantly associated with quality of intrapartum care.ConclusionThe quality of intrapartum care is found poor in the study area. Clients are not getting intrapartum care with state-of-the-art knowledge and current clinical best practices. Input quality, the experience of healthcare providers, friendly care, and continuous training were factors associated with the quality of intrapartum care. Improving the availability of essential inputs, enhancing the performance of healthcare providers through training, and continuous objective monitoring of the standard clinical practices are crucial to ensuring the quality of intrapartum care.